Comparing the indicators of general health among two groups of female Quran memorizers and non- memorizers in Kermanshah, Iran - Mohammad Kian Zarafshani; Azar Midokht Rezaee; Ghazal Zarafshani (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: General health has always been a critical issue in human's life. Religion and religious education is influential in individuals' general health. Thus, the purpose of this descriptive study was to determine the effect of Quran memorization on general health. Method: This study used a simple random sampling procedure to select 106 female Quran memorizers and 91 non-memorizers. With respect to the collected data, the demographic information, such as age, marital status, education, and occupation, was elicited; in addition, general health was measured using the General Health Questionnaire (GHQ-28). The data were analyzed through comparison of means to spot the group differences. In this study, all the ethical issues were considered; moreover, the authors declare no conflict of interest. Results: The results of the study revealed that Quran memorizers were in a better status in terms of general health when compared with the non-memorizers. Accordingly, there were significant differences between the two groups in terms of stress, sleep disorders, depression, and physical signs. Furthermore, a significant difference was detected in terms of social functioning. Conclusion: Since Quran memorizers enjoyed better general health, it could be concluded that extending Quran principles and realizing their effects on individuals' general health could provide greater understanding of Quran and its potential for treating psychological disorders, hence promoting psychological and mental health. For downloading the full-text of this article please click here.